Study on utilization of Tiku fishing port facilities, Agam Regency, West Sumatera Province - Kusniwati '; Jonny Zain; Syafruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
For purpose to identify type, capacity and condition of the facilities, as well as to evaluate thefacilities utilization level at Tiku fishing port. Series survey activities were conducted at Tikufishing port, Agam regency, West Sumatera Province during April 2013. The result shows that theTiku fishing port had complete facilities such as basic, functional and supporting facility.Nevertheless, we were identified the malfunction and useless facilities at Tiku fishing port, such asfresh water tank, cold storage, and fish market hall. The calculation of facilities utilization level was109.35% for fuel tank, 81.48% for Ice and 48.4% for fish market hall.Keywords : Basic facility, functional facility, supporting facility, facilities utilization level, Tikufishing port facilities